Pathological Importance of the Endothelin-1/ETB Receptor System on Vascular Diseases. (30th July 2012) - Kitada, Kento; Ohkita, Mamoru; Matsumura, Yasuo
Abstract : Activation of the endothelin (ET)-1/ET receptor system is involved in the development of vascular diseases such as atherosclerosis, vascular hypertrophy, and restenosis. Some issues still remain unresolved including whether ET receptor antagonists are expected to become the new therapeutic tools for the treatment of vascular diseases. One of the unresolved critical points is the functional role of ET receptor subtypes on each vascular disease, in particular the pathophysiological roles of the ET B receptor. We recently demonstrated that selective inhibition of the ET B receptor system showed harmful effects in the development of neointimal formation after vascular injury. However, there was no apparent difference in the therapeutic effects between a nonselective ET A /ET B receptor antagonist and selective ET A receptor antagonist. These findings indicate that antagonism of the ET A receptor system is essential for suppressing vascular remodeling, irrespective of the presence of ET B -receptor-mediated actions, although the selective ET B receptor antagonist worsens vascular remodeling. In addition, we found that ET receptor systems contribute to sex differences in the severity of vascular disease, thereby suggesting that the efficacy of ET receptor antagonists for vascular diseases may differ between sexes. In this paper, we outline the roles of the ET-1/ET B receptor system on vascular diseases and its sex differences.